Evaluating participant and coordinator satisfaction with telephone assessments. (December 2021) - Pun, Kelly; Sewell, Margaret; Neugroschl, Judith A; Zhu, Carolyn W; Zeng, Xiaoyi; Greenberg, Jonathan; Velasco, Nelly; Sheppard, Faye; Tocco, Carly; Evans, Kirsten; Ardolino, Allison; Meuser, Caroline; et al.
Abstract: Background: In response to the COVID‐19 pandemic, the Alzheimer's Disease Research Center (ADRC) at the Icahn School of Medicine at Mount Sinai began conducting evaluations for the National Alzheimer's Coordinating Center Uniform Data Set (NACC UDS) by telephone in March 2020. The ADRC designed a survey to evaluate participant and research coordinator satisfaction with telephone evaluations. Method: Following UDS evaluations, participants rated their satisfaction on 5 items: voice quality on telephone, respect for privacy, degree of comfort using the telephone, and confidence that the information collected was accurate. Coordinators were asked to gauge their satisfaction on similar items. To calculate satisfaction scores, responses were assigned values: "Very" = 3, "Fairly" = 2, and "Not at all" = 1. Maximum satisfaction score was 15 for participants and 18 for coordinators. Result: Data was available for 130 participants evaluated by telephone between March 2020 and January 2021. Of these, 68.5% were female, 53.7% were white, with an average age of 76.4 and 16 years of education. 74% of participants had a Global Clinical Dementia Rating (CDR) score of 0; 22% CDR 0.5; 4% CDR 1. Participants with CDR >1 were evaluated by caregiver interviews without testing, and those with CDR=1 were offered testing at the discretion of their family and examiners. Average total satisfaction rating was 14.2/15 for participants and 16.8/18 for coordinators. 98% of participants felt their privacy was "very" respected (mean 2.98/3). When looking at global CDR scores, 89.6% of participants with CDR=0 and 88.2% with CDR ≥0.5 were "very" confident in the accuracy of the information collected. In contrast, coordinators were "very" confident in the accuracy of their evaluation 84.4% of the time when participants had a CDR=0 and 67.7% of the time when participants had a CDR ≥0.5. Conclusion: Overall satisfaction with telephone evaluations was high, but participant and coordinator confidence in the accuracy of assessments varied, with coordinator satisfaction lower for more cognitively impaired participants. Future work will analyze satisfaction with ongoing remote assessments and evaluate the impact of additional demographic and diagnostic variables.